Child Sex Tourism: A Case Study in Surabaya, Indonesia. Issue 1 (March 2022) - Bah, Yahya Muhammed; Artaria, Myrtati D.; Suen, Mein-Woei
This article provides a case study of child sex tourism (CST) in Surabaya, Indonesia. CST cases are difficult to surface because the victims of CST are such vulnerable human beings. Victims of CST need a variety of forms of support for their recovery and reintegration. This article contends that social, economic, political, technological, and individual factors cause CST. It examines the negative impacts of CST, which are medical, social, psychological, and physical in nature. It also reveals that the techniques used for CST recruitment are fake promises, debt bondage, emotional abuse, counterfeit love, drug addiction, physical abuse, gifts and favors. The elimination of CST calls for ending certain depraved cultural practices and beliefs, rehabilitation and reintegration of the victims, proactive anti-CST government policies and programs, enactment and effective enforcement of tough laws prohibiting CST, prosecution of the offenders, raising public awareness about the ills of CST, providing education for all children, the provision of national identification documents to all children, and strict border controls to prevent the trafficking of children for sex tourism.